2005
DOI: 10.1007/s10577-005-1007-4
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of C-heterochromatin and telomeric DNA in two representative groups of small apes, the genera Hylobates and Symphalangus

Abstract: The course of chromosome evolution in small apes is still not clear, though painting analyses have opened the way for elucidating the puzzle. Even the C-banding pattern of the lar-group of gibbons (the genus Hylobates) is not clarified yet, although our previous studies suggested that lar-group gibbons have a unique C-banding pattern. We therefore made observations to establish C-banded karyotypes of the agile gibbons included in the lar-group. The data were compared with those of siamangs (the genus Symphalan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
(43 reference statements)
1
18
0
Order By: Relevance
“…These duplications appear to have expanded in concert with the satellite sequence creating a higher-order tandem array structure of several hundred copies in each species. Since subterminal heterochromatic blocks have also been reported among the lesser apes (Wijayanto et al 2005), we tested pCht satellite probes on gibbon metaphase chromosomes and observed no hybridization signal above background (data not shown). Combined, these data strongly suggest that the heterochromatic caps have evolved independently in both chimpanzee and gorilla and possibly all ape species.…”
Section: Subterminal Capsmentioning
confidence: 93%
“…These duplications appear to have expanded in concert with the satellite sequence creating a higher-order tandem array structure of several hundred copies in each species. Since subterminal heterochromatic blocks have also been reported among the lesser apes (Wijayanto et al 2005), we tested pCht satellite probes on gibbon metaphase chromosomes and observed no hybridization signal above background (data not shown). Combined, these data strongly suggest that the heterochromatic caps have evolved independently in both chimpanzee and gorilla and possibly all ape species.…”
Section: Subterminal Capsmentioning
confidence: 93%
“…For karyotyping of N. bengalensis , we used DAPI (4',6-diamidino-2-phenylindole, Sigma, St. Louis, Mo., USA) bands, which are very similar to G-bands (due to a common affinity for AT-rich DNA segments) [Sumner, 1990], and are formed through DNA denaturation treatment at pH 12.5 [Wijayanto et al, 2005]. To check the characteristics of the constitutive heterochromatin (Cbands) of the slow loris forms, a slightly modified version of Sumner's [1972] C-banding method was used.…”
Section: Dapi-and C-banding Analysismentioning
confidence: 99%
“…There is another example in the Hominoidea superfamily: we have previously found that chromosomes of the siamang (Symphalangus syndactylus (SSY)) carry large-scale constitutive heterochromatin at their ends (Wijayanto et al, 2005). This species is a small ape inhabiting the Malay peninsula and Sumatera island in South East Asia.…”
Section: Introductionmentioning
confidence: 99%